Prospecting of livelihoods alternative to tobacco growing in southwestern Paraná - Perondi, Miguel Angelo; Zotti, Cleimary Fatima; Kiyota, Norma; Schervinski Villwock, Ana Paula (Science & Technology Journals, 2011)
From diversification strategies, tobacco farmers and former tobacco producers can improve income and quality of life for their families in rural areas. The initial assumption of this study was that the livelihoods based on diversification of income contribute to greater Independence of income obtained from tobacco production. In the end, it was observed that the tobacco farmers of the southwestern region of Paraná, Brazil, define a set of income sources that keeps the possibility of reconverting the area cultivated with tobacco, although income is not the only parameter to be considered by the families who would like to change their activity. The decision making for the reconversion of this area occurs when two issues are highlighted: a) obtainment of a new source of income consistent with that achieved from tobacco, as that observed in this study through the inclusion of milk production, poultry integration, a non-agricultural strategy, or addition of value; b) obtainment of a better quality of life, whether through the acquisition of a job that poses lower health risk to their families and provides reduction in the painfulness of work or in the total demand of the workforce required, or through other factors considered important by the families.